Transforming Welfare Through Digital Connectivity: Empirical Evidence from Indonesia - Khusniati, Navi'ah (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The development of digital transformation offers considerable potential for poverty alleviation. This study examines the determinants of provincial poverty in Indonesia by analyzing panel data from 34 provinces over an eleven-year period. To obtain consistent and robust estimates in diagnostic test, a fixed effects estimator with Driscoll–Kraay standard errors is employed. The findings reveal that education has the most significant impact on poverty reduction, followed by internet access, electricity access, and economic growth, underscoring the critical role of human capital development and digital connectivity in improving household welfare. In contrast, unemployment, the expansion of oil palm plantations, and provincial GDP per capita are associated with notable increases in poverty, reflecting labor market inflexibilities and non-inclusive growth dynamics. The Gini index is not statistically significant, suggesting that short-term fluctuations in inequality do not substantially affect provincial poverty outcomes. These results highlight the need for policies that expand digital infrastructure, enhance educational attainment, and promote inclusive sectoral development while strengthening governance in resource-dependent regions.